2020
DOI: 10.3389/fnins.2020.00208
|View full text |Cite
|
Sign up to set email alerts
|

Twice-Daily Theta Burst Stimulation of the Dorsolateral Prefrontal Cortex Reduces Methamphetamine Craving: A Pilot Study

Abstract: Conclusion: Accelerated twice-daily TBS appears feasible and tolerable at modulating craving and mood changes in abstinent methamphetamine dependence critically while reducing session length. We emphasize the need for a larger randomized controlled trial study with a sham control to confirm these findings and longer duration of clinically relevant follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
(71 reference statements)
1
30
0
Order By: Relevance
“…Also, previous studies showed that using the iTBS parameter [three-pulse 50-Hz bursts at every 200 ms (i.e., at 5 Hz)], 2 s on and 8 s off for 5 min once per day, with 900 pulses in total, at 100% RMT, 5 days/week, 20 daily sessions, over the left DLPFC ( 12 ), or parameter [three-pulse 50-Hz bursts at every 200 ms (i.e. at 5 Hz)], 2 s on and 8 s off for 3 min once per day, with 600 pulses in total, at 70% RMT, twice-daily TBS over five consecutive days for a total of 10 sessions, over the left or right DLPFC ( 33 ), all reduced the craving scores of MUD patients compared with those before intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies showed that using the iTBS parameter [three-pulse 50-Hz bursts at every 200 ms (i.e., at 5 Hz)], 2 s on and 8 s off for 5 min once per day, with 900 pulses in total, at 100% RMT, 5 days/week, 20 daily sessions, over the left DLPFC ( 12 ), or parameter [three-pulse 50-Hz bursts at every 200 ms (i.e. at 5 Hz)], 2 s on and 8 s off for 3 min once per day, with 600 pulses in total, at 70% RMT, twice-daily TBS over five consecutive days for a total of 10 sessions, over the left or right DLPFC ( 33 ), all reduced the craving scores of MUD patients compared with those before intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments reduced craving similarly suggesting the faster iTBS would be easier and more cost effective to apply in a clinical setting. In a methamphetamine treatment seeking sample, Zhao et al (2020) reported reduced craving in each group that received one of three rTMS dlPFC protocols (left iTBS, left cTBS, or right cTBS) suggesting any TBS intervention could be effective. This adds to recent findings that the general historical understanding that stimulation protocols have opposite effects (Pascual-Leone et al, 1998;Huang et al, 2005) suggesting effects are not universal (Liu et al, 2020;Steele, 2020) The final known unknown addressed in this special issue relates to the state of the participant while receiving the rTMS intervention.…”
Section: Overview Of the Special Issuementioning
confidence: 97%
“…Moreover, these results extended previous understanding of fundamental brain circuits involved in addiction cycle and opened for a principled way to develop individualized treatment in SUDs. Prior works from our lab have focused on stimulating the dorsolateral prefrontal cortex (DLPFC), a hub of frontal-striatal circuitry that is dysfunctional in SUD individuals (Liu et al, 2017 , 2019 ; Shen et al, 2017 ; Zhao et al, 2020 ). Our results have manifested through either activation of left DLPFC or inhibition of the right DLPFC may reduce craving and alleviate symptoms of depression in methamphetamine dependents (Zhao et al, 2020 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Prior works from our lab have focused on stimulating the dorsolateral prefrontal cortex (DLPFC), a hub of frontal-striatal circuitry that is dysfunctional in SUD individuals (Liu et al, 2017 , 2019 ; Shen et al, 2017 ; Zhao et al, 2020 ). Our results have manifested through either activation of left DLPFC or inhibition of the right DLPFC may reduce craving and alleviate symptoms of depression in methamphetamine dependents (Zhao et al, 2020 ). Another strand studies from Hanlon lab have suggested that stimulating left frontal areas can induce selective changes in ventromedial prefrontal cortex (VMPFC), the striatum, and ACC thus change drug cue reactivity in cocaine dependent- and alcohol dependent patients (Hanlon et al, 2015 , 2016 , 2017 , 2018 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%